2017
DOI: 10.1149/2.1121706jes
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Li(Ni1-x-yMnxCoy)O2Positive Electrode Materials and Coatings on Parasitic Heat Flow as Measured by Isothermal Microcalorimetry, Ultra-High Precision Coulometry and Long Term Cycling

Abstract: Isothermal microcalorimetry is used to investigate the effect of different Li(Ni 1-x-y Mn x Co y )O 2 materials (NMC442, NMC532, NMC622) and coatings (Al 2 O 3 and a proprietary high voltage coating) on parasitic reactions that occur in Li-ion pouch type cells. NMC/graphite pouch cells were prepared with a typical organic carbonate-based electrolyte containing a well-known additive blend and were tested up to 4.4 V at 40 • C. A new method of extracting the parasitic heat flow during both charge and discharge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…An earlier microcalorimetry study on the parasitic heat flow in various coated NMC/NG cells with PES211 electrolyte found that NMC622A/NG cells had a much larger parasitic heat flow than NMC622B/NG cells but performed similarly in long term cycling (just as for the blue data in Figures 13b and 13e), suggesting the presence of shuttle-like reactions in NMC622A/NG cells. 24 These shuttle-like reactions may be responsible for keeping the cell impedance small (See Figure 14c). The entire suite of experiments presented in this paper for the NMC532 cells have not yet been applied to the NMC622 cells.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier microcalorimetry study on the parasitic heat flow in various coated NMC/NG cells with PES211 electrolyte found that NMC622A/NG cells had a much larger parasitic heat flow than NMC622B/NG cells but performed similarly in long term cycling (just as for the blue data in Figures 13b and 13e), suggesting the presence of shuttle-like reactions in NMC622A/NG cells. 24 These shuttle-like reactions may be responsible for keeping the cell impedance small (See Figure 14c). The entire suite of experiments presented in this paper for the NMC532 cells have not yet been applied to the NMC622 cells.…”
Section: Resultsmentioning
confidence: 99%
“…where to other chemical reactions. These formulations have extensively been used for investigating the entropic heat of intercalation materials 45 and more recently the parasitic heat in Li-ion cells 30,[46][47][48][49] .…”
Section: Methodsmentioning
confidence: 99%
“…Such behaviour is typical for classical electrochemical intercalation reactions. 26,30 Understanding the exact shape of entropic heat flow is beyond the scope of this study, as it may be related to many aspects of the cathode material, such as the changes in Ru-Ru bond distance ordering 23 , charge ordering, Li vacancy ordering, or the shape of the ⁄ profile (Supp.…”
Section: Thermodynamic Considerationsmentioning
confidence: 99%
“…The same well-established conclusions can be made 10 cycles after the preferred protocol (rank the red points bottom to top) and 20 cycles after the standard formation (rank the points left to right): i) cells with single crystal NMC532 positive electrodes and artificial graphite negative electrodes are better than all those with polycrystalline NMC622 positive electrodes and natural graphite negative electrodes; 35 ii) cells with the ternary additive blend PES211 outperform cells with 2% VC; 29 iii) within cells of the same chemistry, the CIE increases with increasing cycling voltage; 29 iv) in cells with PES211, the Al 2 O 3 -coated positive electrodes outperform those with the proprietary "high voltage" coating. 36 These results suggest that a UHPC experiment, to rank new cells with different chemistries, can be shortened to 10 cycles, if the preferred formation protocol were used. Figure 2 shows that after 20 cycles, most cells formed with the preferred protocol have lower CIEs than the cells cycled with the standard protocol (all the blue points are below the dashed line).…”
Section: Resultsmentioning
confidence: 97%